Regional Development Planning and Policy in the Aspects of Vulnerability and Disaster Resilient Cities: A Review - Latue, Theochrasia; Latue, Philia C; Sihasale, Daniel A; Rakuasa, Heinrich (Nusantara Journal of Behavioral and Social Science, 2023)
Disaster management in the world has undergone a paradigm change that is from responsive to preventive, from sectoral to multi-sector, from government responsibility solely to joint responsibility, centralization to decentralization and from emergency response to disaster risk reduction. Based on 6 directives of the President of the Republic of Indonesia delivered during the Rakornas PB (Disaster Management) at surabaya, February 2, 2019 one of which is "Regional development planning must be based on aspects of DRR (Disaster Risk Reduction)". Disaster risk-based regional development planning aims to reduce the impact of disaster risk including, threats, vulnerabilities, and capacity. Vulnerability assessment in areas that have the potential to experience disaster events is one of the important factors that must be reviewed in disaster mitigation efforts. Vulnerability assessment with the concept of data from wisdom allows local policymakers to recognize their specific situation in the broader context of a similar situation, providing regional perspectives and important connections between regions. Based on the efforts that have been integrated between the program into city spatial planning, it is hoped that it can increase the resilience of the City in facing disasters and adapt to climate change. Abstrak: Penanggulangan bencana di dunia telah mengalami perubahan paradigma yaitu dari responsif menjadi preventif, dari sektoral menjadi multi sektor, dari tanggung jawab pemerintah semata menjadi tanggung jawab bersama, sentralisasi menjadi desentralisasi dan dari tanggap darurat menjadi pengurangan risiko bencana. Berdasarkan 6 arahan Presiden Republik Indonesia yang disampaikan pada saat Rakornas PB (Penanggulangan Bencana) di surabaya, 2 Februari 2019 salah satunya adalah "Perencanaan pembangunan daerah harus berbasis pada aspek PRB (Pengurangan Resiko Bencana)". Perencanaan pembangunan daerah berbasis risiko bencana bertujuan untuk mengurangi dampak risiko bencana yang meliputi, ancaman, kerentanan, dan kapasitas. Penilaian kerentanan pada wilayah yang berpotensi mengalami kejadian bencana merupakan salah satu faktor penting yang harus dikaji dalam upaya mitigasi bencana. Penilaian kerentanan dengan konsep data dari kearifan memungkinkan para pembuat kebijakan lokal untuk mengenali situasi spesifik mereka dalam konteks yang lebih luas dari situasi yang sama, memberikan perspektif regional dan hubungan penting antar wilayah. Berdasarkan upaya yang telah diintegrasikan antara program tersebut ke dalam perencanaan tata ruang kota, diharapkan dapat meningkatkan ketangguhan Kota dalam menghadapi bencana dan beradaptasi terhadap perubahan iklim.